Unveiling the salinity tolerance potential of Armenian Dandur (Portulaca oleracea L.) genotypes: Enhancing sustainable agriculture and food security - Gohar Margaryan; Abhishek Singh; Hrant Khachatryan; Vishnu D Rajput; Tatiana Minkina; Dimitrios Petropoulos; Athanasios Kriemadis; Athanasios Alexiou; Mohamed S. Elshikh; Abd El-Zaher M.A. Mustafa; Karen Ghazaryan (Journal of King Saud University: Science, 2024)
This study examines the adaptation of an undocumented halophyte, Dandur, to salt stress in different soil mediums. The Dandur plant physiological, morphological, and biochemical analyses show that it can withstand salinity stress. Dandur plants grown in clay and clay loam soil experienced significant decreases in height and stem diameter under extreme salinity conditions compared to non-saline soil. The fresh weight of root and shoot decreased by 70.4% and 84.8%, respectively, and dry weight by 48.5% and 79.7%. These findings underscore the importance of maintaining saline soil conditions for plant growth. Dandur unique ability to avoid dehydration and maintain growth traits, particularly in clay soil, holds promise for further exploration in agricultural research and food security-related issues caused by climate change in saline areas of Armenia and other European countries.